Quantitative 18F-AV1451 Brain Tau PET Imaging in Cognitively Normal Older Adults, Mild Cognitive Impairment, and Alzheimer's Disease Patients - Zhao, Qian; Liu, Min; Ha, Lingxia; Zhou, Yun; , Alzheimer's Disease Neuroimaging Initiative; Weiner, Michael W.; Aisen, Paul; Weiner, Michael; Aisen, Paul; Petersen, Ronald; Jack, Clifford R.; Jagust, William; et al. (Frontiers in Neurology, 2019)
Recent tau Positron Emission Tomography (PET) allows assessment of regional neurofibrillary tangles deposition in human brain. 18F-AV1451 is characterized by high selectivity for pathologic tau aggregates. The objectives of the study are 1) to quantitatively characterize regional brain tau deposition measured by 18F-AV1451 PET in cognitively normal older adults (CN), mild cognitive impairment (MCI) and AD participants; 2) to evaluate the correlations between CSF biomarkers or Mini-Mental State Examination (MMSE) and standardized uptake value ratio (SUVR); and 3) to evaluate the partial volume effects on 18F-AV1451 brain uptake. Methods: The study included total 115 participants (CN=49, MCI=58 and AD=8) from the Alzheimer’s Disease Neuroimaging Initiative (ADNI). Preprocessed 18F-AV1451 PET images, structural MRIs, and demographic and clinical assessments were downloaded from the ADNI database. Voxelwise partial volume correction (PVC) on PET images was introduced. PVC and non-PVC SUVR images were compared. The correlation between SUVR and MMSE, CSF total tau (t-tau) and phosphorylated tau (p-tau) were also assessed. Results: 18F-AV1451 prominently specific binding was found in the amygdala, entorhinal cortex, parahippocampus, fusiform, posterior cingulate, temporal, parietal and frontal brain regions. Most SUVRs showed significantly higher uptake of 18F-AV1451 in AD than MCI and CN participants. SUVRs of small regions like amygdala, entorhinal cortex and parahippocampus were statistically improved by PVC in groups (p<0.01). Although there was an increasing tendency of SUVRs in MCI compared with CN group, no significant difference of 18F-AV1451 deposition was found between CN and MCI brains with or without PVC (p>0.05). Declined MMSE score was observed with increasing 18F-AV1451 binding in amygdala, entorhinal cortex, parahippocampus and fusiform. CSF p-tau was positively correlated with 18F-AV1451 deposition. Conclusion: The typical deposition of 18F-AV1451 tau PET imaging in AD brain was found in amygdala, entorhinal cortex, fusiform and parahippocampus, and they were strongly associated with cognitive impairment and CSF biomarkers. 18F-AV-1451 PET imaging could not differentiate the MCI from CN population. More tau deposition related to decreased MMSE score and increased CSF p-tau level . PVC improved the results of tau deposition and correlation studies in small brain regions and suggested to be routinely used in 18F-AV1451 tau PET quantification.